PELATIHAN MENULIS POSTER PENDIDIKAN BERBASIS APLIKASI CANVA DI ERA NEW NORMAL BAGI GURU PENDIDIKAN ANAK USIA DINI (PAUD) SE-KOTA TEGAL - M. Arif Budiman Sucipto; R. Samidi; syamsul anwar (CV. Multi Kreasi Media, 2022)
The Covid-19 pandemic has changed the fabric of the world community. In order to prevent the spread of the corona virus outbreak, people are encouraged and even forced to stay at home. School, work and even worship are recommended to be done at home. Work requires us to always apply the new nomal style, including in the world of education. So it takes creativity and innovation in designing learning. Based on the problems with PAUD teachers throughout the City of Tegal, a solution needs to be given. One of the solutions offered is training in writing posters based on the Canva application. Poster writing training to provide knowledge or insight related to education, as well as practice on images and appropriate color selection.